Impact of maternal posture on fetal physiology in human pregnancy: a narrative review - Kember, Allan J.; Anderson, Jennifer L.; House, Sarah C.; Reuter, David G.; Goergen, Craig J.; Hobson, Sebastian R. (Frontiers in Physiology, 2024)
In numerous medical conditions, including pregnancy, gravity and posture interact to impact physiology and pathophysiology. Recent investigations, for example, pertaining to maternal sleeping posture during the third trimester and possible impact on fetal growth and stillbirth risk highlight the importance and potential clinical implications of the subject. In this review, we provide an extensive discussion of the impact of maternal posture on fetal physiology from conception to the postpartum period in human pregnancy. We conducted a systematic literature search of the MEDLINE database and identified 242 studies from 1991 through 2021, inclusive, that met our inclusion criteria. Herein, we provide a synthesis of the resulting literature. In the first section of the review, we group the results by the impact of maternal posture at rest on the cervix, uterus, placenta, umbilical cord, amniotic fluid, and fetus. In the second section of the review, we address the impact on fetal-related outcomes of maternal posture during various maternal activities (e.g., sleep, work, exercise), medical procedures (e.g., fertility, imaging, surgery), and labor and birth. We present the published literature, highlight gaps and discrepancies, and suggest future research opportunities and clinical practice changes. In sum, we anticipate that this review will shed light on the impact of maternal posture on fetal physiology in a manner that lends utility to researchers and clinicians who are working to improve maternal, fetal, and child health. Figure 1. PRISMA flow diagram outlining the study selection process.Research articles pertaining to the impact of maternal posture on the cervix, uterus, placenta, umbilical cord, amniotic fluid, and fetus can be generally divided into 1) those that consider the impact of maternal posture at rest and 2) those that consider the impact of maternal posture during various activities. As such, we present these aspects separately. Furthermore, we organize the former category of results based on general obstetric entities beginning with the cervix, followed by the uterus, placenta, umbilical cord, amniotic fluid, and finally, the fetus.